Negotiating professional and personal biographies in a liquid world: creating space for reflexive innovation in career counselling. Issue 5 (19th October 2016) - Reid, Hazel; West, Linden
ABSTRACT: This paper explores the constraints to innovative, creative and reflexive careers counselling in an uncertain neo-liberal world. We draw on previously reported research into practitioners' use of a narrative model for career counselling interviews in England and a Europe-wide auto/biographical narrative study of non-traditional learners in universities. The latter draws on a number of narrative interviews with an asylum seeker, to debate whether such a way of working with people, 'in a clinical style', offers contextualised insight into people's struggles to construct a career and a methodology for doing so. The paper also examines the difficulties of creating a 'good enough' professional, psychosocial space for experimentation with creative approaches in a marketised guidance world, where more is expected from less.